2021
DOI: 10.3390/ijerph18041517
|View full text |Cite
|
Sign up to set email alerts
|

Irregular Work Hours and the Risk of Sleep Disturbance Among Korean Service Workers Required to Suppress Emotion

Abstract: Although a necessity in a modern society, irregular work schedule can lead to sleep problems. We investigated the effect of work schedule irregularity on sleep disturbance of 17,846 Korean service workers using the fifth Korean Working Conditions Survey. The odds ratio (OR) and 95% confidence interval (CI) for sleep disturbance occurrence were calculated through a multiple logistic regression model. The adjusted ORs for moderate and severe sleep disturbances for those with irregular work hours were 2.11 (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Qiu et al [48] revealed that the pooled prevalence of sleep disturbances was estimated at 39% among Chinese health professionals while Xia et al [49] showed that the pooled prevalence of sleep disturbances among Chinese doctors and nurses and doctors was 35% and 43%, respectively. Sleep and the timing of sleep are regulated by the circadian rhythms and sleep homeostasis process through the regulation of cortisol and melatonin levels, with cortisol levels in shift workers being higher during sleep and lower when awake compared to levels in regular daytime workers [51,52] The current meta-analysis found that OSA was associated with risk of anxiety, CVD, DM, depression, GERD, and PTSD, while insomnia was associated with risk of depression, anxiety, and PTSD. These findings agree with those of previous studies that found that sleep disturbances 8including insomnia and OSA) were associated with high risk of diabetes mellitus, obesity CVD, hypertension, stroke, depression, and anxiety [53,54].…”
Section: Prevalence and Associated Comorbidities Of Sleep Disorders A...mentioning
confidence: 77%
“…Qiu et al [48] revealed that the pooled prevalence of sleep disturbances was estimated at 39% among Chinese health professionals while Xia et al [49] showed that the pooled prevalence of sleep disturbances among Chinese doctors and nurses and doctors was 35% and 43%, respectively. Sleep and the timing of sleep are regulated by the circadian rhythms and sleep homeostasis process through the regulation of cortisol and melatonin levels, with cortisol levels in shift workers being higher during sleep and lower when awake compared to levels in regular daytime workers [51,52] The current meta-analysis found that OSA was associated with risk of anxiety, CVD, DM, depression, GERD, and PTSD, while insomnia was associated with risk of depression, anxiety, and PTSD. These findings agree with those of previous studies that found that sleep disturbances 8including insomnia and OSA) were associated with high risk of diabetes mellitus, obesity CVD, hypertension, stroke, depression, and anxiety [53,54].…”
Section: Prevalence and Associated Comorbidities Of Sleep Disorders A...mentioning
confidence: 77%
“…In prospective observational cohort studies, poor worktime control has been associated with increased risk of psychological distress [15,16] and depressive symptoms [17,18]. Unpredictable and irregular work schedules have also been linked to poor sleep quality [16,19] and poor mental health [4]. In addition, work-life conflict has been more common in employees who work > 40 h per week [5] or have short intervals (<11 h) [5] between work shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Irregular working hours can lead to sleep disorders and suppress emotions at work according to the fifth Korean Working Conditions Survey (Yun & al, 2021). Data from the Third European Working Conditions Survey (EWCS) conducted in 2000 show that the most favorable effects on health and psycho-social well-being can be observed when higher flexibility is combined with lower variability of working hours (Costa, Sartori and Akerstedt 2006).…”
Section: Irregular Working Hours and Health Risksmentioning
confidence: 99%